Biodegradation of Synthetic Polymers by Fungi - Khan, M.R.; Arshad, M.; Raza, S.A. (Asian Journal of Chemistry, 2012)
The work deals with an important environmental issue i.e., the disposal of plastic wastes. Polyethylene, nylon-6,6 and poly lactic acid were selected as substrates and checked for their biodegradation by fungal species such as Aspergillus niger, Aspergillus orhyzae, Rhizopus orhyzae, Rhizopus oligosporus and Trichoderma viride. Biodegradation was monitored by following the changes in pH, biomass and weight loss. All species failed to degrade polyethylene and nylon-6,6. Polylactic acid, of course, was consumed by all the fungal species.